2009
DOI: 10.1021/jp906352e
|View full text |Cite
|
Sign up to set email alerts
|

C−X···H Contacts in Biomolecular Systems: How They Contribute to Protein−Ligand Binding Affinity

Abstract: The hydrogen bond acceptor capability of halogens has long been underappreciated in the field of biology. In this work, we have surveyed structures of protein complexes with halogenated ligands to characterize geometrical preferences of C-X...H contacts and contributions of such interactions to protein-ligand binding affinity. Notably, F...H interactions in biomolecules exhibit a remarkably different behavior as compared to three other kinds of X...H (X = Cl, Br, I) interactions, which has been rationalized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 62 publications
2
89
0
Order By: Relevance
“…In recent time, also stimulated by the fact that bromine is increasingly used as an easily detectable substituent at small organic ligands used in crystallographic fragment-based lead discovery, a number of protein-ligand complexes have been determined with exceptionally short bromine-tooxygen distances. 3,4 As a prominent example, the ultrahigh-resolution complex of aldose reductase with the brominated ligand IDD 594 (0.66 Å resolution) was investigated by charge density studies. 5 They render the interaction of a Thr113 O γ and a bromine atom as a direct, strongly polarized and electrostatically driven contact.…”
Section: Introductionmentioning
confidence: 99%
“…In recent time, also stimulated by the fact that bromine is increasingly used as an easily detectable substituent at small organic ligands used in crystallographic fragment-based lead discovery, a number of protein-ligand complexes have been determined with exceptionally short bromine-tooxygen distances. 3,4 As a prominent example, the ultrahigh-resolution complex of aldose reductase with the brominated ligand IDD 594 (0.66 Å resolution) was investigated by charge density studies. 5 They render the interaction of a Thr113 O γ and a bromine atom as a direct, strongly polarized and electrostatically driven contact.…”
Section: Introductionmentioning
confidence: 99%
“…Several specific intermolecular forces involved in ligand recognition and binding by protein receptors have been investigated in detail by means of the hybrid QM/MM methodology [24][25][26]. These works confirmed that, if reasonably collocated with a MM context, it is possible to apply the expensive QM method to treat the nonbonding interactions of interest in the whole biomacromolecular framework.…”
Section: Introductionmentioning
confidence: 68%
“…Since the theory behind the various DFT functionals was clarified fairly well in the original literature, we herein refer the readers to these references for those details. Except two more recent DFT methods, M06 and M06-HF, these others tested density functionals that selected here for evaluation were based on at least one of the following reasons: (i) has been used to study the nonbonding interactions in biomolecule systems [25,27,31,52,55,63,64]; (ii) has been used to investigate the bondings involving halogens or halides [65][66][67][68][69], such as halogenwater-hydrogen bridges [70], halogen bondings [71], fluorine bondings [24]; (iii) has been used to determine the intermolecular interaction potentials [72]; (iv) has been used to study the hydrogen bonding systems [73][74][75][76][77]; (v) has been used to predict the binding energies of some dispersion-bound complexes [78].…”
Section: Quantum-mechanical (Qm) Calculationsmentioning
confidence: 99%
“…Based on this analysis in combination with quantum-chemical calculations [108], these authors also stated that there are many more C-Hal . .…”
Section: ← ----------------------------------------------------------mentioning
confidence: 89%
“…Lu et al [70,108] reported additional database searches of different nonbonded halogen interactions in protein-ligand complexes. Based on the dual nature of heavier halogen atoms, the electrophilic "head-on" and nucleophilic "side-on" interactions were both explored.…”
Section: ← ----------------------------------------------------------mentioning
confidence: 99%